2018
DOI: 10.1002/aic.16477
|View full text |Cite
|
Sign up to set email alerts
|

Work and heat integration—A new field in process synthesis and process systems engineering

Abstract: The extension from Heat Integration and design of Heat Exchanger Networks (HENs) to including heating, cooling and power effects from pressure changing equipment has been referred to as Work and Heat Integration and design of Work and Heat Exchange Networks (WHENs). This is an emerging research area in Process Synthesis and PSE, and WHENs represent a considerably more complex design task than HENs. A key challenge is the fact that temperature changes and pressure changes of process streams are interacting. Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Process modeling, simulation, and optimization are crucial to design an industrial tail gas purification process. The process simulation can provide data support for the industrial application of the technology by analyzing the parameters of the system and discover the technical bottleneck in advance. For example, Shiflett et al simulated a CO 2 capture process using pure [C 4 Mim]­[Ac], and the results suggested that 16% energy consumption could be saved compared with traditional processes. Liu et al studied shale gas CO 2 decarbonation process using [C 4 Mim]­[NTf 2 ], and the result indicated that the IL-based process can reduce over 42.8% of energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Process modeling, simulation, and optimization are crucial to design an industrial tail gas purification process. The process simulation can provide data support for the industrial application of the technology by analyzing the parameters of the system and discover the technical bottleneck in advance. For example, Shiflett et al simulated a CO 2 capture process using pure [C 4 Mim]­[Ac], and the results suggested that 16% energy consumption could be saved compared with traditional processes. Liu et al studied shale gas CO 2 decarbonation process using [C 4 Mim]­[NTf 2 ], and the result indicated that the IL-based process can reduce over 42.8% of energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The reader is also referred to comprehensive state-of-the-art reviews on the HEN/WEN/WHEN matter carried out by Fu et al [34] and Yu et al [35]. These include key thermodynamic insights, fundamental concepts, challenges and opportunities on the field.…”
Section: Introductionmentioning
confidence: 99%
“…Nair et al [32] developed a model comprising streams with phase change and without pre-identifying streams as hot, cold, HP or LP, which were defined via optimization. Additionally, the interested reader can find reviews on WHI including possible opportunities and challenges in the works of Fu et al [33] and Yu et al [34].…”
Section: Introductionmentioning
confidence: 99%